Musashi-2 contributes to myotonic dystrophy muscle dysfunction by promoting excessive autophagy through miR-7 biogenesis repression - Maria Sabater-Arcis; Ariadna Bargiela; Nerea Moreno; Javier Poyatos-Garcia; Juan J. Vilchez; Ruben Artero (Elsevier, 2021)
Skeletal muscle symptoms strongly contribute to mortality of myotonic dystrophy type 1 (DM1) patients. DM1 is a neuromuscular genetic disease caused by CTG repeat expansions that, upon transcription, sequester the Muscleblind-like family of proteins and dysregulate alternative splicing of hundreds of genes. However, mis-splicing does not satisfactorily explain muscle atrophy and wasting, and several other contributing factors have been suggested, including hyperactivated autophagy leading to excessive catabolism. MicroRNA (miR)-7 has been demonstrated to be necessary and sufficient to repress the autophagy pathway in cell models of the disease, but the origin of its low levels in DM1 was unknown. We have found that the RNA-binding protein Musashi-2 (MSI2) is upregulated in patient-derived myoblasts and biopsy samples. Because it has been previously reported that MSI2 controls miR-7 biogenesis, we tested the hypothesis that excessive MSI2 was repressing miR-7 maturation. Using gene-silencing strategies (small interfering RNAs [siRNAs] and gapmers) and the small molecule MSI2-inhibitor Ro 08-2750, we demonstrate that reducing MSI2 levels or activity boosts miR-7 expression, represses excessive autophagy, and downregulates atrophy-related genes of the UPS system. We also detect a significant upregulation of MBNL1 upon MSI2 silencing. Taken together, we propose MSI2 as a new therapeutic target to treat muscle dysfunction in DM1.